2019
DOI: 10.33545/comed.2019.v2.i2b.18
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket expenditure on diabetes care in an urban population of Tamil Nadu: A community based study

Abstract: Background: Diabetes is a life-long commitment both to the patient and to the provider. Healthcare cost of diabetes is high since it requires close monitoring to prevent dangerous complications that may further increase the healthcare cost. Aim: To assess the out-of-pocket expenditure on diabetes among diabetic patients in urban Tamil Nadu. Methods: A cross-sectional study was conducted among 180 diabetic patients in Thoothukudi Corporation. Study tool used was a semi-structured interview based questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…This is consistent with another study from India which reported that expenditure increased with duration of diabetes 26 . An increasing trend in OOPE was observed with the presence of complications ( Table II ) and the number of complications ( Supplementary Table I ); this was in keeping with other studies that reported expenditure proportionately increasing with the number of complications 28 , 29 . Furthermore, the input-wise distribution of OOPE was assessed ( Supplementary Table III ) and majority (63%) of the expenditure was found to be incurred on medicines, which is consistent with a number of other studies in India 28 , 29 .…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with another study from India which reported that expenditure increased with duration of diabetes 26 . An increasing trend in OOPE was observed with the presence of complications ( Table II ) and the number of complications ( Supplementary Table I ); this was in keeping with other studies that reported expenditure proportionately increasing with the number of complications 28 , 29 . Furthermore, the input-wise distribution of OOPE was assessed ( Supplementary Table III ) and majority (63%) of the expenditure was found to be incurred on medicines, which is consistent with a number of other studies in India 28 , 29 .…”
Section: Discussionsupporting
confidence: 89%